Group in‐course assessment promotes cooperative learning and increases performance. Issue 3 (3rd September 2013) - Pratten, Margaret K.; Merrick, Deborah; Burr, Steven A.
<x xml:space="preserve">Abstract</x> The authors describe and evaluate a method to motivate medical students to maximize the effectiveness of dissection opportunities by using In‐Course‐Assessments (ICAs) to encourage teamwork. A student's final mark was derived by combining the group dissection mark, group mark for questions, and their individual question mark. An analysis of the impact of the ICA was performed by comparing end of module practical summative marks in student cohorts who had, or had not, participated in the ICAs. Summative marks were compared by two‐way ANOVA followed by Dunnets test, or by repeated measures ANOVA, as appropriate. A cohort of medical students was selected that had experienced both practical classes without (year one) and with the new ICA structure (year two). Comparison of summative year one and year two marks illustrated an increased improvement in year two performance in this cohort. A significant increase was also noted when comparing this cohort with five preceding year two cohorts who had not experienced the ICAs (P <0.0001). To ensure that variation in the practical summative examination was not impacting on the data, a comparison was made between three cohorts who had performed the same summative examination. Results show that students who had undertook weekly ICAs showed significantly improved summative marks, compared with those who did not (P <0.0001). This approach to ICA promotes engagement with learning resources in an active, team‐based, cooperative learning environment. Anat Sci Educ 7: 224–233. © 2013 American Association of Anatomists.